Ceremonies and manifestations of the celebration of Ramadan in the Ottoman era "Istanbul and Cairo as a model" - Al-Jawadi, Ghassan (Humanities Journal of University of Zakho, 2022)
The Celebrated Ceremonies and Rituals of Ramadan during the Ottoman Period “Istanbul and Cairo example” Historical studies that deal with the social side of a community in the Ottoman period, is regarded as a vivid area for researchers to explore the norms and traditions of the Islamic people. These traditions include the religious ceremonies, the formal and the public ones, among these ceremonies are the ones held during the month of Ramadan, fasting month. This fasting month has a role in showing the nature of the relationship between individuals and the state and the community and the government. During these ceremonies, the Sultan and his family, the key figures in the society like Alssadar Alaatham, the governors, judges and the religious scholars all take part in these ceremonies and celebrate them. The religious institutions had a role in maintaining these rituals which did not contradict with the Alshariah, the Islamic Law. Similarities and variances among the religious ceremonies and rituals, which were held during the month of Ramadan, are obvious, though some of these ceremonies have faded away w,hile others are still practiced till nowadays. This piece of research which comes under the title ‘The Celebrated Ceremonies and Rituals of Ramadan in Istanbul and Cairo during the Ottoman Period’ examines the rituals and norms held during the month of Ramadan, those rituals and norms that are part of the social life of the community in both cities ; Istanbul and Cairo . The research has concluded a number of outcomes among which are; the ruling government at that time paid these ceremonies a great attention and celebrated it with people.. The research emphasizes the rich social rituals inherited in the Islamic communities. These rituals were the main topics the foreign travelers dealt with in their writings as they followed the daily ceremonies to celebrate the month of Ramadan. , there is a need for more researches that address the positive sides of the traditions and rituals followed during the month of Ramadan in the Ottoman period .